Understanding Redeployment During the COVID-19 Pandemic: A Qualitative Analysis of Nurse Reported Experiences - Erin Kennedy DNP, RN; Patrick Kennedy DNP, RN, ACNPC-AG; Joanna Hernandez DNP, RN, AGACNP-BC; Kelly Shakoor DNP, RN, FNP-BC; Kristen Munyan DNP, RN, FNP-BC (SAGE Publishing, 2022)
Introduction The COVID-19 pandemic disrupted healthcare working conditions causing the redeployment of nurses. Redeployment refers to assigning healthcare workers to units or specialty areas where they do not regularly work. Objective The purpose of this study was to explore the lived experiences of redeployed nurses during the COVID-19 pandemic from April 27, 2020 to May 7, 2020. Methods Data collection occurred through a cross-sectional survey with demographic items and a single open-ended item. This open-ended item was part of a larger study regarding work conditions during the initial COVID-19 surge in the spring of 2020 in the Midwest United States (US). This analysis was performed separately due to the volume of qualitative responses and details provided. The survey was posted in private social media groups, and 298 nurses participated, 117 shared open-ended responses. Participants were asked what type of unit they worked on before COVID-19 and what unit they were deployed to. Findings Twenty-three (19.7%) reported deployment to COVID-designated units. Twenty-eight (23.9%) participants reported deployment to a unit outside of their specialty. Sixteen (13.7%) reported deployment from a non-critical care unit to an intensive care unit. Three major themes developed from the open-ended responses: (1) challenges related to their scope of practice and specialization, (2) challenges with interpersonal dynamics, and (3) challenges related to the environment. Conclusion The described challenges caused some nurses to report primarily negative experiences regarding redeployment during the COVID-19 pandemic. The findings add to the existing literature regarding redeployment and the vulnerability hospitals and their staff face during a disaster or pandemic-related events, such as COVID-19. Ultimately, aiding in the development of new policies to facilitate effective pandemic response in the future that would support nurses to participate in redeployment in a safe and nontraumatic way, is necessary.